CHEMICAL COMPOSITION OF ESSENTIAL OILS OF UMBELLIFERAE SPECIES FROM THE CENTRAL AND NORTHEASTERN REGIONS OF KAZAKHSTAN - Ozek, G.; Suleimenov, Y.; Ishmuratova, M. Yu; Rakhmadieva, S. B.; Baser, K. H. C. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Essential oils of the Umbelliferae species from the Central and North-eastern regions of Kazakhstan were analyzed by GC-FID and GC/MS methods. Eryngium planum L., Cnidium dubium (Schkuhr) Schmeil et Fitschen, Conioselinum tataricum Hoffm, Heracleum sibiricum L. and Ferula soongarica Pall. ex Schult., collected at flowering stage, were subjected to hydrodistillation in a Clevenger type apparatus to obtain essential oils. Most of the studied oils were predominated by monoterpene type constituents with alpha-terpinyl acetate (24.8%), alpha-pinene (18.2%) and limonene (12.6%) in Cnidium dubium; gama-terpinene (39.7%), p-cymene (19.4%) and beta-pinene (15.7%) in Conioselinum tataricum; (E)-beta-ocimene (41.5%), myrcene (31%) and (Z)-beta-ocimene in Heracleum sibiricum; alpha-pinene (17.9%) and myrcene (16.0%) in Ferula soongarica, as main constituents. The oil of Eryngium planum was dominated by germacrene type sesquiterpenes with germacrene D (25.7%), germacrene B (5%) and bicyclogermacrene (3.7%) as major representatives. Among the monoterpenes group, trans-chrysanthenyl acetate (18.9%) was the major constituent.